ELECTIONS AND ADMINISTRATIVE RESOURCE: AN EXPERIENCE OF SCIENTIFIC AND LAW-POLITICAL EXPERTISE - Дмитришин, А.Д. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The main contents of article are resolution of the made on request of public prosecutor’s office expertise of pre-legal inquest materials. Its main task to be an argument in the process of establishing the issue in criminal affair, bring a suit on abuse by district administration officials during elections of Ukrainian President.